Analysis Of Judge's Decision On Notary Tort In South Jakarta District Court (Case Study No. 124/PDT.G/2017/PN.Jkt.Sel) - Ma'ruf Akib; Amin Purnawan (Jurnal Akta, 2019)
The purpose of this research is 1) To know the Judges considerations in determining Notary Torts in South Jakarta District Court, 2) To determine the Decision Execution Judge Effects of Torts committed Notary in South Jakarta District Court.The method in this research is descriptive. This type of research is normative. The method used is qualitative analysis, namely data obtained through fieldwork and research literature then arranged systematically, and then analyzed qualitatively to achieve clarity issues to be discussed. The data is then analyzed using a theoretical and interpretive positive law which has been poured and then deductively conclude to address existing problems.Based on the results of research that the judge in analyzing the case with No. 124/PDT.G/2017/PN.Jkt.Sel seen from the evidence presented as witnesses, documentary evidence, conjecture, confession or oath that is revealed in the trial are: Defendant 1 and Defendant V and co-Defendant 1 and Defendant II helped found guilty of Torts; Plaintiff is the legal owner of the disputed land Right No. 3747/Pondok Pinang, covering an area of 310 M.2, Pictures situation 24-0201994 date No. 1242/1994; Sale and Purchase Deed before a Notary Noor Kholid Adam, SH., MH between Andrei Widjaya with Ir. Sugandi, canceled Based on Law; Mortgage Ranked First No. 5204/2016 based APHT PPAT Noor Kholis Adam, SH., MH, registered in the name of Standard Chartered Bank with registered office in Branch Jakarta dated August 29, 2016 is the Disability Law, Illegal, not have binding legal force; As a result of the implementation of decisions of law in case No. 124 / PDT.G / 2017 / PN.Jak.Sel relating to tort which did by Notary is null and void, with all the legal consequences of Notary Deed and the Co-Defendants, namely: Sale and Purchase Deed No. 202/2016 dated May 23, 2016, made before PPAT Noor Kholis Adam, SH., MH; Property Ownership Deed of Credit Agreement (KPP) No. 872 / MRG / V / 16 dated May 23, 2016; Property Title Deed of Credit Agreement (KPP) No. 873 / MRG / V / 16 dated May 23, 2016; Power of Attorney Imposing Mortgage No. 203/2016 dated May 23, 2016 of Notary PPAT Noor Kholis Adam, SH., MH .; Power of Attorney to charge Encumbrance No. 256/2016 dated June 22, 2016, made before PPAT Noor Kholis Adam, SH., MH. Granting Mortgage Deed No. 301/2016 dated July 21, 2016, made before PPAT Noor Kholis Adam, SH., MH .; Owned right certificate No. 3747/Pondok Pinang Size 310 M.2, Pictures Situation No. 1242/1994 dated February 24, 1994 on behalf of Andrie Widjaya burdened security rights to Standard Chartered Bank.Keywords: Judge's Decision; Torts; Notary.